Tingkat Serangan dan Kehilangan Hasil Akibat Penyakit Grasserie pada Sentra Persuteraan Alam Sulawesi Selatan - Sitti Nuraeni; Astuti Arif; Edwin NL (Fakultas Kehutanan, Universitas Hasanuddin, 2018)
Grasserie disease is one of the serious diseases caused by viruses. Its symptoms generally appear in the last instar of silkworm larvae or just before the formation of the cocoon. This study aimed to determine the level of attack, yield losses and dispersal patterns of grasserie at three sericulture center in South Sulawesi, Districs (Wajo, Soppeng and Enrekang). At each location 10 farmers were selected purposively as respondents. Direct observation was conducted to the farmer’s rearing rack (on farmer’s rearing bed) of silkworm using five replications. The results showed that the attack rates of grasserie were categorrised as very slight, ranging from 3.06 to 3.72 kgs of yield losses per each box with a uniform pattern of disease spread. Reared of silkworms in accordance with standard operating procedures can reduce the rate of grasserie disease to avoid losing larger cocoon yields.